The Influence of 1-Butanol and Trisodium Citrate Ion on Morphology and Chemical Properties of Chitosan-Based Microcapsules during Rigidification by Alkali Treatment - Sudipta Chatterjee; Fabien Salaün; Christine Campagne (Marine Drugs, 2014)
Linseed oil which has various biomedical applications was encapsulated by chitosan (Chi)-based microcapsules in the development of a suitable carrier. Oil droplets formed in oil-in-water emulsion using sodium dodecyl sulfate (SDS) as emulsifier was stabilized by Chi, and microcapsules with multilayers were formed by alternate additions of SDS and Chi solutions in an emulsion through electrostatic interaction. No chemical cross-linker was used in the study and the multilayer shell membrane was formed by ionic gelation using Chi and SDS. The rigidification of the shell membrane of microcapsules was achieved by alkali treatment in the presence of a small amount of 1-butanol to reduce aggregation. A trisodium citrate solution was used to stabilize the charge of microcapsules by ionic cross-linking. Effects of butanol during alkali treatment and citrate in post alkali treatment were monitored in terms of morphology and the chemical properties of microcapsules. Various characterization techniques revealed that the aggregation was decreased and surface roughness was increased with layer formation.